Perception, Self, and Zen: On Iris Murdoch and the Taming of Simone Weil - Caprioglio Panizza, Silvia (MDPI, 2023)
How do we see the world aright? This question is central to Iris Murdoch's philosophy as well as to that of her great source of inspiration, Simone Weil. For both of them, not only our action, but the very quality of our being depends on the ability to see things as they are, where vision is both a metaphor for immediate understanding and a literal expression of the requirement to train our perception so as to get rid of illusions. For both, too, the method to achieve this goal is attention. For both, finally, attention requires a dethronement of the self, considered as the source of illusion. In this paper I investigate what moral perception means for each of these philosophers and how it operates through attention and its relationship with the self. I will show that, despite many striking similarities, Murdoch's project does not equal 'Weil minus God', but offers a different concept of the self, a different understanding of its removal, and therefore a different picture of attention and moral perception. In evaluating both views, I will gesture towards a third way represented by Zen Buddhism, which both philosophers variously consider but do not embrace.
Vnímání, já a zen: O Iris Murdochové a zkrocení Simone Weilové
Keywords: moral perception; attention; self; Iris Murdoch; Simone Weil; Zen Buddhism; morální vnímání; pozornost; já; Iris Murdochová; Simone Weilová; zenový buddhismus